The strategic importance of Cooperation in the development of the economy of the sea - Miguel Marques (European Regional Science Association (ERSA), 2015)
As the need for growth and development increases, due to the necessary search for more new job opportunities for layers of society that are struggling to find work, greater attention has been placed on the level of added value generated by internal resources. In the case of Portugal, one of the most important internal resources that has been looked at with greater attention is the sea. For the past 10 years, there has been greater awareness about activities associated with the sea; however, the implementation of new projects in the field has been considered slow. In this context, the aim of this document is to analyse the status of cooperation in the Portuguese Economy of the Sea, including the breakdown of cooperation levels by each sea sector (Universities/Investigation Centers, Public Administration, Shipbuilding and Ship Repair/ Naval Maintenance industries, Maritime Transports, Ports, Logistics and Shipping industries, Fishing, Aquaculture and Fisheries industry, Entertainement, Sports, Tourism and Culture industries, Financial Entities , Municipalities) and the links between cooperation and the evolution of the sector. The methodology followed is the description the results of inquiries to top managers of the economy of the sea and compilation of numeric data, based in the author? professional experience in maritime economy and entrepreneurship, namely in the production of HELM ? PwC Economy of the Sea Barometer (Portugal).
Keywords: 330; sea economy; cooperation; Portugal